Partisanship and public opinion of COVID-19: does emphasizing Trump and his administration's response to the pandemic affect public opinion about the coronavirus?. (31st May 2021) - Spälti, Anna Katharina; Lyons, Benjamin; Mérola, Vittorio; Reifler, Jason; Stedtnitz, Christine; Stoeckel, Florian; Szewach, Paula
ABSTRACT: Does emphasizing the pandemic as a partisan issue polarize factual beliefs, attitudes, and behavioral intentions concerning the SARS-CoV-2/COVID-19 pandemic? To answer this question, we conducted a preregistered survey experiment with a "questions as treatment" design in late March 2020 with 1587 U.S. respondents recruited via Prime Panel. Respondents were randomly assigned to answer several questions about then-president Donald J. Trump and the coronavirus (including receiving an information cue by evaluating one of Trump's tweets) either at the beginning of the survey (treated condition) or at the end of the survey (control condition). Receiving these questions at the beginning of the survey had no direct effect on COVID-19 factual beliefs, attitudes, and behavioral intentions.